The Importance of Management Control Systems (MCS) in Small and Medium Enterprises (SME), An Empirical Literature Review - Bienmali Kombate (AFEBI Accounting Review, 2016)
The main focus in this paper is the importance of Management Control Systems (MCS) in Small and Medium Enterprises (SMEs). The research is based on empirical literature by collecting and interpreting researchers finding on the important role that play MCS in SMEs. A greater control systems implementation can create/added a value and influencing stakeholders to practice concrete actions to reduce costs derived from the exploitation in SMEs.Keywords: Management Control Systems, Small and Medium Enterprises